A Lightweight Image Encryption Algorithm Based on Elliptic Curves and a 5D Logistic Map - Rashid , Abdullah A.; Hussein, Khalid A. (Iraqi Journal of Science, 2023)
Cryptography can be thought of as a toolbox, where potential attackers gain access to various computing resources and technologies to try to compute key values. In modern cryptography, the strength of the encryption algorithm is only determined by the size of the key. Therefore, our goal is to create a strong key value that has a minimum bit length that will be useful in light encryption. Using elliptic curve cryptography (ECC) with Rubik’s cube and image density, the image colors are combined and distorted, and by using the Chaotic Logistics Map and Image Density with a secret key, the Rubik’s cubes for the image are encrypted, obtaining a secure image against attacks. ECC itself is a powerful algorithm that generates a pair of public and private elements, and we generate secret key values ​​with the help of the above key pair. This algorithm is applied to smart cards, sensors, and wireless network security. Whereas, the test results indicate that the highest value for PSNR is 7.9641, while the highest values for UACI and NPCR are 35.3721 and 99.9992, respectively. The encoding and decoding speeds reach 0.1561 and 0.1532 seconds, respectively.